Osoba i metoda personacji - Gałecki, Sebastian (Śląskie Studia Historyczno-Teologiczne, 2014)
The term “person” from the beginning was the foundation of both Christian anthropology and theology. Today, we are inclined to understand this notion in the way proposed by Karol Wojtyla and other representatives of the so-called Christian personalism. This paper has two goals: to familiarize the reader with a theory of the person (which had a significant influence on twentieth-century personalism), developed by nineteenth-century theologian and philosopher, John Henry Newman, and to describe and verify Newman’s “method of personation”. These two elements – the concept of the person and the method of personation – form an original and inspiring anthropology. While the first one is a kind of a classical theory of the person, the second is an important novelty in philosophy and theology. “Method of personation” is a very brave thesis that appears throughout the works of C ardinal Newman: the value of a theory largely depends on the authorities supporting it. Can the history and theology find evidence of the fundamental role of outstanding persons in identifying and spreading the truth?